A fluorescence-based assay for monitoring clinical drug resistance. Issue 11 (2nd August 2012) - Deniset-Besseau, Ariane; Miannay, François-Alexandre; Laplace-Builhé, Corinne; Vielh, Philippe; Lécart, Sandrine; Lwaleed, Bashir A; Eschwege, Pascal; Fontaine-Aupart, Marie-Pierre
Abstract : Background and aims: Multidrug resistance (MDR) limits effectiveness in treating malignancy by modifying internalisation and/or externalisation of drugs through cancer cell membranes. In this study we describe an assay to monitor patients' responses to chemotherapy. Methods: The assay is based on the fluorescent properties of doxorubicin alone as well as in combination with methotrexate, vinblastine, doxorubicin and cisplatin (MVAC). The slide-based cell imaging technique was first optimised using a panel of breast and urothelial cancer cell lines and then extended to fine needle breast aspiration biopsy and urine cytology. Results: The drug fluorescence behaviour observed on smears of clinical specimens is identical to that obtained using fixed cultured cells. The fluorescence of sensitive cells to chemotherapy is mainly localised in the nucleus, whereas resistant cells show a weak fluorescence signal localised in the cytoplasm. The difference in terms of fluorescence intensity is also highlighted through fluorescence spectra. Conclusions: The results suggest that the assay provides clinically valuable information in predicting responses to doxorubicin and/or MVAC therapy. Originally set up on a confocal microscope, the assay was also effective using a standard epifluorescence microscope; as such it is technically simple, reliable and inexpensive.